CONTRIBUTION OF ROHANA KUDUS TO EMPOWERING MINANGKABAU WOMEN THROUGH VOICES AND WORKS - Ermagusti Ermagusti; Arrasyid Arrasyid; Rahmad Tri Hadi (Marwah: Jurnal Perempuan, Agama dan Jender, 2023)
This study aims to describe and analyze the contribution of Rohana Kudus in empowering Minangkabau women through her voice and work, both in the fields of religion, education, journalism, economics, social life, politics, and other fields. This study uses the gender deconstruction method, namely nurture. Called nurture because social and cultural factors create gender attributes and form stereotypes of a certain gender in society from generation to generation (culture). The results showed that due to the encouragement and demands to promote Minangkabau women, Rohana Kudus established the "Kerajinan Amai Setia" (KAS) school which teaches various household crafts such as sewing, cooking and so on. In addition, she managed to publish a weekly newspaper for Minangkabau women known as “Soenting Melajoe”. It is because of her struggle that Rohana Kudus can be recorded as the first woman journalist in West Sumatra.